Complex Multimorbidity and Breast Cancer Screening Among Midlife and Older Women: The Role of Perceived Need. (17th May 2019) - Warner, David F; Koroukian, Siran M; Schiltz, Nicholas K; Smyth, Kathleen A; Cooper, Gregory S; Owusu, Cynthia; Stange, Kurt C; Berger, Nathan A
Abstract: Background and Objectives: There is minimal survival benefit to cancer screening for those with poor clinical presentation (complex multimorbidity) or at advanced ages. The current screening mammography guidelines consider these objective indicators. There has been less attention, however, to women's subjective assessment of screening need. This study examines the interplay between complex multimorbidity, age, and subjective assessments of health and longevity for screening mammography receipt. Research Design and Method: This cross-sectional study uses self-reported data from 8, 938 women over the age of 52 in the 2012 Health and Retirement Study. Logistic regression models estimated the association between women's complex multimorbidity (co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes), subjective health and longevity assessments, age, and screening mammography in the 2 years before the interview. These associations were evaluated adjusting for sociodemographic and behavioral factors. Results: Both age and complex multimorbidity were negatively associated with screening mammography. However, women's perceived need for screening moderated these effects. Most significantly, women optimistic about their chances of living another 10–15 years were more likely to have had screening mammography regardless of their health conditions or advanced age. Discussion and Implications: Women with more favorable self-assessed health and perceived life expectancy were more likely to receive screening mammography even if they have poor clinical presentation or advanced age. This is contrary to current cancer screening guidelines and suggests an opportunity to engage women's subjective health and longevity assessments for cancer screening decision making in both for screening policy and in individual clinician recommendations.